Pendekatan Realistic Mathematics Education Berbantuan Articulate Storyline untuk Meningkatkan Kemampuan Penalaran dan Sikap Percaya Diri - Ariffah, Eko Yunia Nur; Novitasari, Meggy (PTK: Jurnal Tindakan Kelas, 2024)
This study aims to detect the Realistic Mathematics Education (RME) approach assisted by Articulate Storyline that can improve the ability of students reasoning and self-confidence in the material for building class IV SD Negeri Pajang 1. This type of research is classroom action research. This research was conducted with a cycle model. The subject of this study was a class IV student. The data collection technique used in this study is observation, a test in the form of a story problem to hone the ability of student reasoning in solving the problem of building space, and a questionnaire to find out the attitude of students' confidence and documentation. The data in this study were analyzed by descriptive analysis. The results of this study indicate an increase in the ability of students reasoning and self-confidence through realistic mathematics education (RME) assisted by Articulate Storyline. This is evidenced by the initial ability to reach an average value of 56.6, in the first cycle reached an average value of 71, and cycle II reached an average value of 87.2. Meanwhile, the initial results of students' confidence reached 29.16%, cycle I reached 45.83%and the second cycle reached 87.50%.